INTENTION PENYANDANG DISABILITAS DALAM MENGGUNAKAN PRODUK PERBANKAN SYARIAH DI INDONESIA - Hendratmoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The market share of Islamic banking in Indonesia has only reached 5.95% and there are still many people with disabilities, especially those who are Muslim, who have not used Islamic banking products in Indonesia.The purpose of this study is to determine what factors influence the intention or intention of people with disabilities to use Islamic banking products. This study is different from previous studies because it only focuses on persons with disabilities and the population drawn is persons with disabilities in Jabodetabek (Jakarta, Bogor, Depok, Tangerang and Bekasi).The research approach uses quantitative research by taking a sample of 126 respondents with disabilities in the Jabodetabek area. Sampling was carried out using purposive sampling during the period December 2020.From this research, the conclusion is that the factors attitude, reliogisity, knowledge and place have a positive and significant effect on intention. Keywords: Intention, Attitude, Reliogisity, Knowledge and Place